2023
DOI: 10.1002/pssb.202300216
|View full text |Cite
|
Sign up to set email alerts
|

Demonstration of Enhanced Saturable Absorption in Upconverter Integrated MoS2 Heterostructure Thin Film Using Nanopulsed Green Laser

Murugan Durairaj,
T. Chidambaram Sabari Girisun

Abstract: Upconverter/MoS2 heterostructure thin films were fabricated by simple hydrothermal technique. X‐ray diffraction and Raman studies assures the formation of upconverter/ MoS2 heterostructure. FESEM and HRTEM revealed that the nanobelt structured MoS2 mingled with trapezoid structure fluoride upconverters and sphere shaped oxide upconverters in films. Bandgap of MoS2 heterostructure films increased to 3.21 eV (NaYF4: Yb, Er), 3.72 eV (YF3: Yb, Er), 3.54 eV (Y2O3: Yb, Er) and 3.43 eV (CeO2: Yb, Er) than 1.98 eV (M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 61 publications
1
0
0
Order By: Relevance
“…It was previously reported that nanomaterials with higher linear absorption coefficients possess larger nonlinear optical absorption. 83,84 It should be noted that Nb 4 C 3 MXene showed higher linear absorbance at 1900 nm wavelengths than that at 1560 nm wavelengths according to our measured linear absorption curve (Fig. 2d) and calculated curve (Fig.…”
Section: Resultssupporting
confidence: 53%
“…It was previously reported that nanomaterials with higher linear absorption coefficients possess larger nonlinear optical absorption. 83,84 It should be noted that Nb 4 C 3 MXene showed higher linear absorbance at 1900 nm wavelengths than that at 1560 nm wavelengths according to our measured linear absorption curve (Fig. 2d) and calculated curve (Fig.…”
Section: Resultssupporting
confidence: 53%